Revolutionizing English language instruction for special education students through engaging and meaningful experiences - Angga Pratama Armadi Putra (Indonesian Journal of Foreign Language Studies, 2025)
Content and Language Integrated Learning (CLIL) offers a promising approach to enhancing the education of children with special needs. By seamlessly integrating subject matter and language learning, CLIL creates a rich and engaging environment that fosters cognitive, social, and emotional development. Through collaborative teaching, visual aids, and hands-on activities, students with special needs can develop a deeper understanding of subjects while improving their language proficiency. Research has shown that CLIL not only boosts students' academic performance but also increases their motivation and engagement in learning. This study aims to evaluate the effectiveness of CLIL in improving English language skills and academic achievement among students with special needs in inclusive classrooms. By examining previous research and analyzing implementation data, this study will provide valuable insights to inform the development of effective CLIL practices and policies.